Wear of the implant connection with zirconia and titanium abutments - José, A. R. (2019)
Background: Classify and quantify the wear of the implant and abutment interface simulating a loose screw situation. Methods: Nine external connection titanium implants were split into 4 groups: Group A (no hexagon titanium abutment), Group B Titanium abutment (with hexagon) (n=3), Group C Zirconia abutment with hexagon (n=3) and Group D mix abutments (n=2). All components were individually weighted and the rotational freedom for each pair was access before and after testing. The specimens were tested an Instron 8874 fitted with a dynamic load cell with a torque capacity of 100Nm and a precision of 0.5% from 1% of the full scale. They were loaded with a sinusoidal rotational angle that was different for each group (A= 6º, B= 3.3º, C= 0.835º, D=6.6 º), 4 Hz, for 250.000 cycles. After testing all components were photographed with a SEM. Spearman’s correlation analysis was made. Results: Regardless of angle and materials the rotational freedom increased in all groups. Volume loss with zirconia abutment was more than double than with a titanium abutment. Conclusion: The loose screw in implant prosthesis may lead to the wear of the hexagon on both components. This wear is sufficient to compromise the connection beyond repair